Perceptions and use of electronic cigarettes in pregnancy. Issue 1 (27th January 2017) - McCubbin, Andrea; Fallin-Bennett, Amanda; Barnett, Janine; Ashford, Kristin
Abstract: Use of electronic cigarettes (e-cigs) is quickly growing in the United States, despite the unknown health implications and unregulated device contents. Although research is emerging around e-cigs in general, there continues to be a lack of scientific evidence regarding the safety and risks of e-cig use on maternal and fetal health, even though adverse health effects of nicotine on maternal and fetal outcomes are documented. This review summarizes existing perceptions of e-cig use in pregnancy, based on the limited number of publications available, and highlights the necessity of conducting additional research in this field of public health. Authors conducted a literature search of scientific peer-reviewed articles published from January 2006 to October 2016, comprising more than a decade of research. Search keywords include 'tobacco use', 'electronic cigarette(s)' and 'pregnancy'. Fifty-seven publications were identified, narrowed to fifteen by screening title/abstract for potential relevance, with seven articles chosen for final inclusion. Of these seven studies, most participants not only believed e-cigs pose risks to maternal and child health but also perceived e-cigs as a safer and potentially healthier alternative to traditional cigarettes, and may assist with smoking cessation. Further research is needed to determine health implications and provide clinical guidelines for e-cig use in pregnancy.